Analysis of factors affecting sustainable performance in construction sites using fuzzy AHP-WASPAS methods. (2022) - Bathrinath, S.; Mohan, S.; Koppiahraj, K.; Bhalaji, R.K.A.; Santhi, B.
Abstract: Sustainability is having our own needs without adjusting any problem related activities. Mainly we need three factors to find the sustainable related problems in working area .We need to identify the best alternative method to find the problem in day to day work activities. Sustainable construction was only practice of creating a best alternative way to solve the problems. The environment and working area major problems was to be identified in the construction site by using above fuzzy AHP method. The modern world sustainable is the best solution for solving construction and industry related problems easily. Our main motive is to reduce environment related problems and to reduce that sustainability is the best way to find suitable solutions for this problem. By using MCDM method and we have to find 18 alternatives and 5 criteria for Job safety analysis (JSA) and Failure mode effective analysis (FMEA).Analytical Hierarchical Process and WASPAS method is used to find the rank the problems and to solve in construction site.